Alloantibodies and Drug-Induced Immune Hemolytic Anemia in Liver Transplantation. (30th June 2011) - Allanki, Surekha Devi
Abstract : Red blood cell alloantibodies can cause severe delayed hemolysis, despite immunosuppression which they receive posttransplantation. A female patient with Hepatitis C-related chronic liver disease reported to our center for liver transplantation. During preoperative evaluation, she was found to have significant red blood cell alloantibodies which gave rise to problems during pre transfusion compatibility test. Stringent measures were taken by the transplant team to minimize blood loss during surgery. It was decided to have lower transfusion trigger for red cell transfusion, and blood conservation was done by intraoperative red cell salvage and use of antifibrinolytic agent. During immediate postoperative period, she developed drug-related immune hemolytic anemia. Presence of both warm autoantibodies and alloantibodies posed a big challenge for us to get cross-match compatible blood. She received 22 units of crossmatch compatible red cell transfusions during her hospital stay, which was uneventful. Hence, we reported this case.